2014
DOI: 10.1038/nm.3750
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant epithelial GREM1 expression initiates colonic tumorigenesis from cells outside the stem cell niche

Abstract: Hereditary mixed polyposis syndrome (HMPS) is characterised by the development of mixed morphology colorectal tumours and is caused by a 40 kb duplication that results in aberrant epithelial expression of the mesenchymal Bone Morphogenetic Protein antagonist, GREM1. Here we use HMPS tissue and a mouse model of the disease to show that epithelial GREM1 disrupts homeostatic intestinal morphogen gradients, altering cell-fate, that is normally determined by position along the vertical epithelial axis. This promote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
228
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 229 publications
(260 citation statements)
references
References 38 publications
21
228
1
Order By: Relevance
“…The GREM1 duplication also confirms that alterations of regions giving rise to amplifications and up‐regulation of expression can have an effect on tumor initiation also in germ‐line cells. The genotype, phenotype, and also the increased expression levels of GREM1 in our family give further support to the suggested role of activation of GREM1 as a cause of initiation and development of colorectal tumors (Jaeger et al, 2012; Davis et al, 2015). …”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The GREM1 duplication also confirms that alterations of regions giving rise to amplifications and up‐regulation of expression can have an effect on tumor initiation also in germ‐line cells. The genotype, phenotype, and also the increased expression levels of GREM1 in our family give further support to the suggested role of activation of GREM1 as a cause of initiation and development of colorectal tumors (Jaeger et al, 2012; Davis et al, 2015). …”
Section: Discussionsupporting
confidence: 86%
“…In our study an activating 16 kb duplication was found upstream of GREM1 . A duplication of approximately 40 kb of an upstream region containing parts of the SCG5 gene and also a region between, but not the GREM1 gene itself, has recently been shown to over express GREM1 in colorectal epithelium (Jaeger et al, 2012; Davis et al, 2015). The GREM1 gene encodes the secreted BMP antagonist Gremlin.…”
Section: Discussionmentioning
confidence: 99%
“…We further show that inhibition of Grem1 significantly reduces the generation of CD34 + CSC-induced spheroids, indicating that secretion of Grem1 by CD34 + CSCs plays a predominant role in maintenance of IESCs. Consistent with this hypothesis, forced expression of Grem1 in epithelial cells is sufficient to disrupt intestinal morphogenic gradients, promoting the persistence or reacquisition of stem cells properties by differentiated epithelial cells (35). The massive epithelial proliferation observed in CD34…”
Section: Here We Identify Cd34mentioning
confidence: 67%
“…Importantly they also observed that deletion of Apc in differentiated enterocytes (using low levels of recombination in AhCre Apc fl/fl mice) caused the formation of small lesions that rarely went on to form tumours (or if they did it was at long latency), thus demonstrating that Lgr5 + stem cells were indeed efficient cells of origin for intestinal cancer (162). This paper seemed to have settled the debate in favour of the bottom-up model, however, two papers then discovered that transformation could occur in Lgr5-negative cells outside of the crypt base stem cell niche, ether in cells with Apc and Kras mutations (163), or those expressing the BMP antagonist Gremlin (164). More recently, the development of a new Cre (carbonic anhydrase), which does not induce in colonic stem cells but only in more differentiated cells, confirmed these results in the colon (165).…”
Section: The Cell Of Origin and Cancer Stem Cellsmentioning
confidence: 99%